Pengaruh Pengembangan Karir, Motivasi Kerja dan Kompetensi Terhadap Kinerja Pegawai Pada Dinas Pariwisata, Kepemudaan dan Olahraga Tanjung Jabung Timur - Ade Jermawinsyah Zebua; Ratumas Hartha Delima; Irfan Widyanto (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
This research is based on the existing phenomena showing that employees have not been able to work optimally in a government agency. The purpose of this study was to find out and obtain a study about the effect of career development, work motivation and competence on employee performance. This research is a quantitative descriptive study with a sample of 39 respondents, while the sampling technique used in this study is saturated sampling. In this study, the independent variables consist of career development, work motivation and competence, while the dependent variable is employee performance. Testing the instrument using validity and reliability tests. While the method of data analysis using multiple linear regression analysis with t test, f test and R².